Challenges for programmatic implementation of killed whole cell oral cholera vaccines for prevention and control of cholera: a meta-opinion. (2nd September 2018) - Chatterjee, Pranab; Kanungo, Suman; Dutta, Shanta
ABSTRACT: Introduction : Cholera remains a public health threat. The development of safe, effective, easy-to-administer, heat-stable, and cheap killed whole cell oral cholera vaccines (OCVs) has provided an additional tool to counter cholera. In this meta-opinion, we review the challenges of delivering OCVs through the existing public health infrastructure in vulnerable areas. Areas covered : We provide an overview of the available vaccines against cholera, the existing evidence about the effectiveness of a two-dose as well as a single-dose OCV strategy. We also highlight the experience from the public health campaigns for OCV deployment. Expert opinion : Several public health experiences have shown the feasibility of incorporating OCVs into the public health response against cholera. Combined with a comprehensive water, sanitation, and hygiene (WaSH) improvement plan, OCVs need to be deployed in identified vulnerable areas, targeting the highest risk groups first. Vaccination programs should not be deployed in lieu of investments in WaSH services, but as a complimentary service in a comprehensive, cholera control intervention package. It has been a challenge to have high two-dose coverage across all eligible recipients, necessitating the adoption of innovative strategies to boost coverage. Longer intervals between doses may help to overcome resource and logistical limitations enabling higher coverage.